Determinant of Audit Quality in A Public Accounting Firm in Sulawesi - Defrianti Ramadani; Andi Agus; Anwar (www.amertainstitute.com, 2024)
This study examines the influence of intellectual intelligence, emotional intelligence, spiritual intelligence, professional ethics, and auditor work experience on audit quality. This study uses primary data sourced from auditors working at Public Accounting Firms in Sulawesi. Data was obtained by distributing questionnaires directly to auditors at 4 public accounting firms in South Sulawesi and sending online questionnaires to auditors located outside South Sulawesi. So that the total respondents used in this study are 50 respondents. Data analysis used the multiple linear regression method with the SPSS (Statistical Product And Sevice Solution) version 22 program with testing using research instrument tests, classical assumption tests, partial significance tests (t test), and simultaneous significance tests (f test). The results of the study prove that Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence, Professional Ethics, and Auditor Work Experience have a positive and significant effect on audit quality. The suggestion in this study is to further improve intellectual intelligence, emotional intelligence, and spiritual intelligence as well as work experience for auditors, for further research can be carried out by adding other variables that have a stronger influence on audit quality, further research is expected to use direct interviews with auditors.